Cardiovascular changes in Smokeless Tobacco Users in a Tertiary Level Hospital (Journal of Medicine, 2016)
Background: Tobacco has close association with cardiovascular parameters such as hypertension and pulse rate. Tobacco can be consumed as cigarette and also as smokeless tobacco. However, the relationship between smokeless tobacco uses on blood pressure remains unknown, especially in tertiary level hospitals.Objective: smokeless tobacco use might have influence on cardiovascular parameters, for instance pulse rate and blood pressure.Methods: This cross-sectional study was carried out to assess cardiovascular changes in among adult male smokeless tobacco (ST) users. For this purpose, 30 male respondents were selected. The participants were selected from medicine out patient department of Dhaka Medical College Hospital. Pulse rate and blood pressure was measured and ST use behaviour was assessed using self-reports. Statistical analysis was done by SPSS17.Results: In this study, the mean (±SD) of pulse rate was 84.07±11.011beat/min. The mean (SD) of systolic blood pressure was 154.50 (SD26.79) mm of and the mean (SD) of diastolic blood pressure was 96.67(SD10.93) mm of Hg in smokeless tobacco users.Conclusion: Mean systolic and diastolic blood pressures were higher in smokeless tobacco users in the tertiary level hospital. However, mean pulse rate was within the normal range.J MEDICINE July 2016; 17 (2) : 61-65